Curriculum Development Strategy for Arabic Lesson at Madrasah Ibtidaiyyah Miftahul Mubtadiin Islamiyyah Banyakan Kediri - Arifin, Moh Aziz; Karim, Abdul Malik (UIN Syekh Wasil Kediri, Indonesia, 2022)
This research examines the Arabic language learning process at MI Miftahul Mubtadiin Islamiyyah Banyakan Kediri which have known the Arabic lessons in early age. Basic level Arabic curriculum or Madrasah Ibtidaiyyah Arabic lessons are taught in a 4th grade students of Madrasah Ibtidaiyyah. However, in fact, the 4th grade students are only taught the Arabic that is already known of Arabic in a basic way. The purpose of this is study: (1) to determine curriculum development strategy for Arabic lesson at MI Miftahul Mubtadiin Islamiyyah Banyakan Kediri, (2) to determine the implementation of curriculum Arabic at MI Miftahul Mubtadiin Islamiyyah Banyakan Kediri. The method used in this study is descriptive qualitative methods and data collection methods used interviews, observation, and documentation. The results of the study explain: (1) curriculum development strategy for Arabic lesson at MI Miftahul Mubtadiin Islamiyyah Banyakan Kediri uses several processes, including: steps to be taken, compiling, strategies to be used, process of program preparation, implementation, and evaluation, (2) implementation of Arabic language curriculum at MI Miftahul Mubtadiin Islamiyyah, mostly located in Kediri city, have gone through a process guided by KMA Number 184 of 2019 concerning Guidelines for Curriculum Implementation in Madrasahs, Ministry of Religion and it was developed by its institution to achieve competent outputs or graduates in the field of Arabic subjects.